2015
DOI: 10.1152/jn.01011.2014
|View full text |Cite
|
Sign up to set email alerts
|

ATP stimulates rat hypothalamic sympathetic neurons by enhancing AMPA receptor-mediated currents

Abstract: Ferreira-Neto HC, Antunes VR, Stern JE. ATP stimulates rat hypothalamic sympathetic neurons by enhancing AMPA receptormediated currents. J Neurophysiol 114: 159 -169, 2015. First published April 22, 2015 doi:10.1152/jn.01011.2014.-We have previously shown that ATP within the paraventricular nucleus (PVN) induces an increase in sympathetic activity, an effect attenuated by the antagonism of P2 and/or glutamatergic receptors. Here, we evaluated precise cellular mechanisms underlying the ATP-glutamate interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
12
1
Order By: Relevance
“…Purinoceptors on neurons in the brain stem and hypothalamus mediate sympathetic nerve activity. 159,160 Brain stem hypoxia contributes to the development of hypertension in the SHR, because of release of ATP resulting in central sympathetic drive leading to increase in systemic arterial blood pressure. 161 Antagonists to these purinoceptors would reduce sympathetic nerve activity resulting in vasodilatation and are therefore potential centrally acting drugs for the treatment of hypertension.…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…Purinoceptors on neurons in the brain stem and hypothalamus mediate sympathetic nerve activity. 159,160 Brain stem hypoxia contributes to the development of hypertension in the SHR, because of release of ATP resulting in central sympathetic drive leading to increase in systemic arterial blood pressure. 161 Antagonists to these purinoceptors would reduce sympathetic nerve activity resulting in vasodilatation and are therefore potential centrally acting drugs for the treatment of hypertension.…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…The predecessor compounds of this drug, cX1846, have all been shown to elevate BDNF levels at doses cX1846 corrects age-related memory issues without exerting unwanted side effects. it would be of considerable clinical interest to investigate Ampakines as a means to up-regulate BDNF in the hypothalamus by positively modulating hypothalamic AMpA receptors (54) since targeted genetic therapy is at its infancy.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Anti-LGI1 antibody inhibits the ligand-receptor interaction between LGI1 and ADAM22/23, resulting in a reduction in synaptic AMPA receptors ( 12 ). Some studies have shown that AMPA receptors in the PVN play an important role in central blood pressure regulation ( 13 , 14 ). Furthermore, the PVN is involved in the central efferent pathway of the autonomic system, which corresponded to the supposed lesion of the OH in our patient.…”
Section: Discussionmentioning
confidence: 99%